Pengaruh praktik kerja industri dan pelayanan informasi bursa kerja khusus BKK terhadap kesiapan kerja siswa kelas XII teknik dan bisnis sepeda motor SMK Walisongo Semarang - Khoirudin, Andi; Mahendra, Sena; Ariwibowo, Bayu (Prosiding Seminar Nasional & Internasional EDUSTEM, 2023)
ABSTRACT Andi Khoirudin. The Influence of Industrial Work Practices and Special Job Exchange (BKK) Information Services on the Job Readiness of Class XII Students in Motorcycle Engineering and Business at SMK Walisongo Semarang. Thesis. Automotive Mechanical Engineering Vocational Education, Faculty of Technology and Vocational Education IVET University Semarang. 2023. 150 Pages. This study aims to 1) To examine the effect of industrial work practices on student work readiness. 2) To examine the effect of special job market information services (BKK) on student work readinessIn this study the authors used quantitative research methods which are classified as ex post facto research. Which only discloses data based on the results of measuring symptoms that already exist naturally in the respondent, with data collection tools in the form of questionnaires and documentation. The results of this study are 1) There is a significant influence of industrial work practices (X1) on student work readiness. This is evidenced by the significant value far below the probability value of 0.000 <0.05. 2) There is a significant influence of BKK information services (X2) on student work readiness (Y). That is the sig value. far below the probability value of 0.000 <0.05. 3) There is a significant influence of industrial work practices (X1) and BKK information services (X2) on student work readiness (Y). That is, with a sig value. probability value 0.000 <0.05. And it is known that the magnitude of the influence is 56.1% and the remaining 43.9% is not examined in this study. Keywords: industrial work practices, BKK information services and job readiness